GROWTH AND YIELD IN SOYBEAN IN DIFFERENT SOWING PERIODS IN THE WEST REGION OF BAHIA - CRUZ, Thyane Viana da; PEIXOTO, Clovis Pereira; MARTINS, Mônica Cagnin (Scientia Agraria, 2010)
The objective of the present work was to evaluate plant and yield development of five soybean cultivars indicated for the Western Region of Bahia in different sowing dates, with different maturation cycles. The essays were installed in the experimental field of the Bahia Foundation, at Maria Gabriela Farm in São Desidério – BA, 2006-2007. The experimental design was in random blocks in 4 x 5 factorial scheme (four sowing dates: first – 11/29/2006, second - 12/14/2006, third - 12/28/2007, fourth - 01/12/2007 and five cultivars: M-SOY 8411, BRS Corisco, BRS 263 [Diferente], BRS Barreiras e M-SOY 9350) with four replications. In order to evaluate plant development the phenological peformance was evalualed during the entire crop cycle and collection of five plants thirty days after emergence (DAE) until full maturation was carried out every two weeks for the determination of dry matter, leaf area, number of leaves and plant height. Yield was obtained by weighing the beans from the useful area of each plot. Sowing date influences plant development and yield of soybean cultivars. The delay of the sowing period promotes to reduction the cycle of soybean cultivars, mainly in the reproductive phase. Ecophysiology, late sowing 28/12/2006 and 12/01/2007 are not favourable to raise yield to soybean in Western Region Bahia.